Destiny of souls eaudiobook New case studies of life between lives. - Newton, Ph.D, Michael (Tantor Media, 2011)
In Destiny of Souls , sixty-seven people just like you recall their life between lives through Dr. Michael Newton's personal work in spiritual hypnotherapy. Based on his groundbreaking research into the afterlife, this book is designed both for those new to afterlife case studies and for fans of Dr. Newton's bestselling first volume, Journey of Souls . Explore the meaning behind your own spiritual memories as you hear the stories of people in deep hypnosis and learn fascinating details about: —Our purpose on Earth —Spiritual settings where souls go after death —The soul-brain connection —Soul mates —Soul travel between lives —Spirit guides —Ways spirits connect with and comfort the living —Why we choose certain bodies